Elevated subgingival temperature infers high bacterial pathogen counts in severe periodontitis - Thomas E. Rams; Jørgen Slots (Wiley, 2024)
Abstract Objectives Periodontal inflammation may be assessed by bleeding on probing and subgingival temperature. This pilot study evaluated the intrapatient relationship between subgingival temperature and selected bacterial groups/species in deep periodontal pockets with bleeding on probing. Materials and Methods In each of eight adults, an electronic temperature probe identified three "hot" pockets with elevated subgingival temperature and three "cool" pockets with normal subgingival temperature among premolars/molars with 6‒10 mm probing depths and bleeding on probing. Microbial samples collected separately from the hot and cool periodontal pockets were cultured for selected periodontal pathogens. Results Hot compared to cool periodontal pockets revealed significantly higher absolute and normalized subgingival temperatures and yielded higher mean proportions of Porphyromonas gingivalis (10.2% for hot vs. 2.5% for cool, p = 0.030) and total red/orange complex periodontal pathogens (48.0% for hot vs. 24.6% for cool, p = 0.012). Conclusions Hot versus cool deep periodontal pockets harbored significantly higher levels of major periodontal pathogens. Subgingival temperature measurements may potentially be useful to assess risk of periodontitis progression and the efficacy of periodontal therapy.